If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5 + -9x) = 31 (5 * 4 + -9x * 4) = 31 (20 + -36x) = 31 Solving 20 + -36x = 31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -36x = 31 + -20 Combine like terms: 20 + -20 = 0 0 + -36x = 31 + -20 -36x = 31 + -20 Combine like terms: 31 + -20 = 11 -36x = 11 Divide each side by '-36'. x = -0.3055555556 Simplifying x = -0.3055555556
| -6+u=-8 | | 6x+10y=162 | | -4(3t-4)+8t=4t-3 | | 13y+19=(9+y)+14 | | 3x-7=8+6(x+1) | | 1/2y=-3x-1 | | 2=10x-18 | | -9(5v+40)= | | (5x+2)(3x^2-23x+30)=0 | | 5r-14=14+r | | X^3-2=17 | | 6x+7y=135 | | 8x-36=26 | | 20a+13(301)=6173 | | x^2-70x+89=0 | | x-15=-40 | | 9r-5=607 | | 1/4=1/20d | | 9x+12x-36+12x=21x-16+15-8x | | 20a+13s=6173 | | .01x^2-.22x+2.9=0 | | -4/3x-10=10 | | 6.5(x-3)=0.5x+15.5 | | 7/8t-5/8=7/6 | | 2z-5y=12 | | 5x+3=-6+2x+24 | | 80=2(4w+5)+2 | | 31-1=5(x+3) | | 12-9x=8-4 | | -2+3y=7 | | 2x-6+5=3x+6 | | 244=2(3w-18)+2 |